Pemodelan Sistem Pendukung Keputusan Dalam Penentuan Rute Distribusi Minimarket Menggunakan Metode Fuzzy - Niko Alifero; Rizki Achmad Darajatun; Sukanta Sukanta (Peneliti.net, 2022)
The purpose of this research is to make a decision support system for determining transportation and distribution routes, and to increase the level of efficiency and simplify the process of determining transportation and distribution routes. This research uses qualitative research. The results showed that 1) Decision support systems in determining distribution routes can be made using the fuzzy method. If the road conditions and traffic density on each road are not much different, then determining the route based on the adjusted speed is no different from determining the route using the closest route approach. 2) Travel time generated by fuzzy modeling can adjust to changes in road conditions and traffic density.